Route-specific effects of desmopressin on bleeding and hyponatremia after kidney biopsy: meta-analysis of intranasal vs. intravenous administration - Zheng, Li; Cai, Zhoujun; Shao, Lina; Zhang, Wei; Zhu, Bin; Ren, Yan (Frontiers in Nephrology, 2025)
BackgroundHemorrhage represents the primary complication associated with kidney biopsy, with post-biopsy bleeding occurring in up to 14% of cases. Some clinicians routinely administer hemostatic agents, such as desmopressin, prior to kidney biopsy to mitigate the risk of significant bleeding. However, the efficacy of this practice remains contentious. Consequently, this meta-analysis was undertaken to assess existing studies regarding the efficacy and safety of desmopressin used before kidney biopsy.MethodsThis systematic review and meta-analysis incorporated both randomized controlled trials and observational studies that examined the outcomes of desmopressin administration prior to percutaneous renal biopsy. Efficacy was measured by the incidence of bleeding events, while safety was assessed through the rate of hyponatremia. A comprehensive search of multiple databases was performed, and the risk of bias was evaluated, and statistical analyses were conducted using appropriate models.ResultsTwelve studies were included. The primary meta-analysis showed no significant reduction in overall bleeding risk with desmopressin (pooled OR 0.71, 95% CI: 0.47 - 1.09; I² = 79%; p = 0.12).Statistically significant differences were observed in the intranasal administration group (pooled OR 0.41;95% CI: 0.28 to 0.60; I 2 = 20%; p < 0.0001)(Fixed effect), the RCT group (pooled OR 0.30; 95% CI: 0.17 to 0.53; I 2 = 0%; p < 0.0001)(Fixed effect), the low bias group (pooled OR 0.53; 95% CI: 0.32 to 0.87; I 2 = 74%; p = 0.01)(Random effect). We conducted statistical analysis on six studies with specific data on hyponatremia, and the pooled OR used fixed model was 2.14 (95% CI: 1.51 to 3.03; I 2 = 28%) (Fixed effect), indicating there was a statistical difference between the two groups (p < 0.0001).ConclusionDesmopressin did not significantly reduce overall bleeding risk after kidney biopsy. While intranasal administration, RCT only and low bias group showed efficacy in subgroup analyses, it carried a significant hyponatremia risk. Route-specific protocols warrant further study.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023391915.